The Problems of Educational Unit Field Experience Program (PPL SP) for PGSD Students During a Pandemic - Tiyas Puji Setianti; Diah Widyani; Tatat Hartati; Rahman Rahman (STAI Hubbulwathan Duri, 2022)
Change suddenly resulting in many educational institutions has not avoid congestion strategy, facilities, and infrastructure held a distance learning or online learning. Limitations of media and the skill to operate the hardware and software as a means and infrastructures major can lead to learning that is done it becomes less efficient. Learning is done online rated less effective, so lowering the interaction between lecturers and students and the impact that was felt by the students, they are difficult to understand the material and ask the material that they have yet to understand due to lack of concentration. This study will use the descriptive survey that seeks to explain or record the conditions that can describe the situation. In line with the research objectives sought to describe the difficulties of the students of teacher training that is being or has been carrying out the course PPL SP in elementary school when the pandemic COVID -19 take place. The Data obtained will be analyzed using descriptive statistics it is selected because it corresponds with the purpose of descriptive method selected. Descriptive statistics serve to interpret the data more easily. Problems faced by students of PGSD Universitas Pendidikan Indonesia in the Campus Area of the Attack, among others, difficulties during the implementation of online learning that includes the process of opening and closing the lesson as well as deliver material to the students. Arouse students ' motivation was to be the task of the student PPL SP that difficult.